Barley responses to combined waterlogging and salinity stress: separating effects of oxygen deprivation and elemental toxicity - Zeng, Fanrong; Shabala, Lana; Zhou, Meixue; Zhang, Guoping; Shabala, Sergey (Frontiers in Plant Science, 2013)
Salinity and waterlogging are two major factors affecting crop production around the world and often occur together (e.g. salt brought to the surface by rising water tables). While the physiological and molecular mechanisms of plant responses to each of these environmental constraints are studied in detail, the mechanisms underlying plant tolerance to their combined stress are much less understood. In this study, whole-plant physiological responses to individual/combined salinity and waterlogging stresses were studied using two barley varieties grown in either vermiculite (semi-hydroponics) or sandy loam. Two weeks of combined salinity and waterlogging treatment significantly decreased plant biomass, chlorophyll content, maximal quantum efficiency of PSII and water content in both varieties, while the percentage of chlorotic and necrotic leaves and leaf sap osmolality increased. The adverse effects of the combined stresses were much stronger in the waterlogging-sensitive variety Naso Nijo. Compared with salinity stress alone, the combined stress resulted in a 2-fold increase in leaf Na+, but a 40% decrease in leaf K+ content. Importantly, the effects of the combined stress were more pronounced in sandy loam compared with vermiculite and correlated with changes in the soil redox potential and accumulation of Mn and Fe in the waterlogged soils. It is concluded that hypoxia alone is not a major factor determining differential plant growth under adverse stress conditions, and that elemental toxicities resulting from changes in soil redox potential have a major impact on genotypic differences in plant physiological and agronomical responses. These results are further discussed in the context of plant breeding for waterlogging stress tolerance.